Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand - Chainthong, Damrong; Sartori, Michel; Boonsoong, Boonsatien (Zootaxa, 2020)
Stylogomphus thongphaphumensis sp. nov. is described from a type series of specimens reared from larvae (holotype ♂, Huai Khayeng, Thong Pha Phum district, Kanchanaburi Province; 14°36′20″N 98°34′38″E, 206 m a.s.l., larva collected on 14.XII.2014; adult emerged on 30.IV.2015). All larvae were collected from the same locality in western Thailand. Description of the larva (based on preserved exuviae) is provided as well. The adult of this species can be distinguished from other Stylogomphus Fraser, 1922, by the morphology of the male anal appendages, pterothoracic pattern, abdominal pattern, male genitalia and female valvula vulvae (detail provided in the differential diagnosis below). This is the first species of Stylogomphus to be described from Thailand. This study also reports the first record of Stylogomphus malayanus Sasamoto, 2001, from Thailand.